Sustainable Economic Development Strategy in Langkat Regency: Challenges and Opportunities - Safrida, Safrida; Lubis, Hasrita; Riana, Zenni; Simatupang, Ahmad Ramadan (Regress: Journal of Economics & Management, 2024)
This study analyzes sustainable economic development strategies in Lalat Regency, focusing on the challenges and opportunities faced. The research methods used include in-depth interviews, participatory observations, and document studies to identify the implementation of strategies in key sectors such as agriculture, tourism, and MSMEs. The results of the study show that Langkat Regency has implemented several positive steps, including the development of sustainable agriculture and nature-based tourism. However, there are significant challenges, such as environmental degradation, social inequality, and lack of supporting infrastructure. Opportunities that can be taken advantage of include the potential for abundant natural resources and support from the central government and international institutions. This study recommends strengthening the capacity of farmers and MSME actors, improving infrastructure, and implementing more inclusive and sustainable policies. In conclusion, to achieve a sustainable economy, Langkat Regency needs to adopt a more coordinated approach and involve all stakeholders to ensure that the economic growth achieved is not only economically sustainable, but also socially and environmentally.